Skin dose saving of the staff in 90Y/177Lu peptide receptor radionuclide therapy with the automatic dose dispenser. Issue 10 (October 2016) - Fioroni, Federica; Grassi, Elisa; Giorgia, Cavatorta; Sara, Rubagotti; Piccagli, Vando; Filice, Angelina; Mostacci, Domiziano; Versari, Annibale; Iori, Mauro
Abstract : Objective: When handling 90 Y-labelled and 177 Lu-labelled radiopharmaceuticals, skin exposure is mainly due to β-particles. This study aimed to investigate the equivalent dose saving of the staff when changing from an essentially manual radiolabelling procedure to an automatic dose dispenser (ADD). Materials and methods: The chemist and physician were asked to wear thermoluminescence dosimeters on their fingertips to evaluate the quantity of Hp(0.07) on the skin. Data collected were divided into two groups: before introducing ADD (no ADD) and after introducing ADD. Results: For the chemist, the mean values (95th percentile) of Hp(0.07) for no ADD and ADD are 0.030 (0.099) and 0.019 (0.076) mSv/GBq, respectively, for 90 Y, and 0.022 (0.037) and 0.007 (0.023) mSv/GBq, respectively, for 177 Lu. The reduction for ADD was significant ( t -test with P <0.05) for both isotopes. The relative differences before and after ADD collected for every finger were treated using the Wilcoxon test, proving a significantly higher reduction in extremity dose to each fingertip for 177 Lu than for 90 Y ( P <0.05). For the medical staff, the mean values of Hp(0.07) (95th percentile) for no ADD and ADD are 0.021 (0.0762) and 0.0143 (0.0565) mSv/GBq, respectively, for 90 Y, and 0.0011 (0.00196) and 0.0009 (0.00263) mSv/GBq, respectively, for 177 Lu. The t -test provided a P -value less than 0.05 for both isotopes, making the difference between ADD and no ADD significant. Conclusion: ADD positively affects the dose saving of the chemist in handling both isotopes. For the medical staff not directly involved with the introduction of the ADD system, the analysis shows a learning curve of the workers over a 5-year period. Specific devices and procedures allow staff skin dose to be limited.